Assessment in the primary care of the State of São Paulo, Brazil: incipient actions in sexual and reproductive health - Mariana Arantes Nasser; Maria Ines Battistella Nemes; Marta Campagnoni Andrade; Rogério Ruscitto do Prado; Elen Rose Lodeiro Castanheira (Universidade de São Paulo, 2017)
ABSTRACT OBJECTIVE The objective of this study is to assess performance in sexual and reproductive health of primary health care services of the Brazilian Unified Health System, in the State of São Paulo, Brazil. METHODS An evaluative framework was built for sexual and reproductive health with the categorization of 99 indicators in three domains: sexual and reproductive health promotion (25), sexually transmitted infections/AIDS prevention and care (43), and reproductive health care (31). This framework was applied to assess the services responses to the questionnaire of Quality Evaluation of Primary Health Care in the Municipalities of São Paulo State (QualiAB), in 2010. Percentages were calculated for positive responses to indicators and performance in the sexual and reproductive health dimension, according to domains, and their contribution to the overall score in sexual and reproductive health (Friedman), relative participation (Dunn), and correlation (Spearman) was verified. RESULTS Overall, 2,735 services participated in the study. They were located in 586 municipalities (distributed throughout the 17 regional health departments of São Paulo), of which 70.6% had fewer than 100,000 inhabitants. The overall average performance of these services for sexual and reproductive health is 56.8%. The actions are characterized by: prenatal with adequate beginning and exams, better organization for immediate rather than for late postnatal care, and selective reproductive planning for some contraceptives; prevention based on specific protection, limitations in the prevention of congenital syphilis, in the treatment of sexually transmitted infections, and in the screening of cervical and breast cancer; specific educational activities, with a restricted vulnerability approach, focus on sexuality over reproduction. The domain of reproductive health has greater participation in the overall score, followed by prevention/care and promotion. The three domains are correlated; the domain of prevention/care has the highest correlation with the other ones. CONCLUSIONS The implementation of sexual and reproductive health in primary health care in the services studied is incipient. The revision of the purpose of the work, the dissemination of technologies, and the investing in permanent education are needed. The evaluative framework built can be used by the sexual and reproductive health program services and management in primary health care, thereby contributing to their actions.